Foreign experience in ensuring of non-interference in the private life of a person in criminal proceedings - D. V. Simonovych; O. V. Blyshchyk (Law and Safety, 2021)
Positive experience in legal regulation of non-interference in private (personal and family) life of a person in criminal proceedings has been studied. The normative prescriptions of international legal acts have been analyzed, which guarantee non-interference in the private (personal and family) life of a person, and provide for cases of lawful restriction of this right. It has been determined that for a long period of time there have been intensive scientific discussions in democratic countries about the extent to which state interference in a person's private life can be allowed, i.e. considered legitimate. The urgency and importance of this issue is due to the fact that the intensification of social and political processes, which began to be connected to the world at the beginning of this century, have significantly influenced the reform of national legislation of Ukraine. The adoption of the Criminal Procedure Code of Ukraine in 2012 was a significant event in this direction, as among the general principles of criminal proceedings, lawmakers provided for non-interference in private life. This is important for participants in criminal proceedings, as the content and form of criminal proceedings must comply with general principles. At the same time, the practice of implementing the provisions of the CPC of Ukraine does not always ensure the rights and freedoms of the individual, in particular non-interference in private life. The current legislation is not able to fully guarantee the successful resolution of certain problems that arise from time to time in the field of criminal justice. All this leads to a growing need of citizens to clearly define the limits of law enforcement intervention in private life. The international community, in particular the European Court of Human Rights, has repeatedly stressed that the rules of law of a restrictive nature must be of high quality, i.e. without ambiguity in their interpretation and application. Otherwise, it violates the right to non-interference in the private life.